2010
DOI: 10.1103/physrevb.82.155405
|View full text |Cite
|
Sign up to set email alerts
|

Dual phononic and photonic band gaps in a periodic array of pillars deposited on a thin plate

Abstract: We study theoretically the simultaneous existence of phononic and photonic band gaps in a periodic array of silicon pillars deposited on a homogeneous thin silica plate. Several lattices, namely, square, triangular, and honeycomb are investigated for a wide range of geometrical parameters. We discuss the most suitable cases for dual phononic-photonic band gaps, especially in comparison to the more conventional structures constituted by a periodic array of holes in a membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 26 publications
(33 reference statements)
0
51
0
Order By: Relevance
“…The latter has been receiving increasing interest for the last few years, as it can exhibit simultaneous photonic and phononic band gaps. [6][7][8][9][10][11][12] Maldovan and Thomas 6 demonstrated this property for an infinite two-dimensional (2D) crystal made of a square or hexagonal lattice of holes in silicon. Sadat-Saleh et al 7 extended this investigation to lithium niobate (LiNbO 3 ) and considered more general lattices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been receiving increasing interest for the last few years, as it can exhibit simultaneous photonic and phononic band gaps. [6][7][8][9][10][11][12] Maldovan and Thomas 6 demonstrated this property for an infinite two-dimensional (2D) crystal made of a square or hexagonal lattice of holes in silicon. Sadat-Saleh et al 7 extended this investigation to lithium niobate (LiNbO 3 ) and considered more general lattices.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, absolute photonic band gaps can be found for more complicated lattices such as boron nitride. 10 Shortly after, it was theoretically demonstrated that a periodic array of silicon pillars deposited on thin homogeneous silica (SiO 2 ) membrane can also be a promising phoxonic system for the three most common lattices, i.e., square, triangular, and honeycomb, 11 especially as concerns the flexibility in the choice of the geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] In addition, we can also use the topology optimization to design PnC bandgaps with the ultra-low mid-frequencies for low frequency sound insulation. 60 Moreover, the topology optimization combined with the symmetry reduction may be suitable for the PxC bandgap engineering 34,[48][49][50][51][52][53][54][55][56][57][58] to construct more PxCs with a strong photon-phonon interaction. This interesting problem is the subject of our ongoing research.…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…2D phoxonic crystal structures have been identified for silicon with air holes and silicon pillars in air [3,4], and for lithium niobate with air holes [6]. 3D phoxonic crystals composed of metal spheres in a dielectric background have been proposed [7], but the dominant material platform is arguably the silicon slab perforated with periodic arrays of sub-micrometer holes [8][9][10] or supporting a periodic array of pillars [11]. Such nanostructures can be precisely manufactured using silicon-on-insulator (SOI) technologies.…”
Section: Introductionmentioning
confidence: 99%